2016
DOI: 10.1038/srep33075
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic structure quantification by using ultrasound Nakagami imaging for assessing liver fibrosis

Abstract: Acoustic structure quantification (ASQ) is a recently developed technique widely used for detecting liver fibrosis. Ultrasound Nakagami parametric imaging based on the Nakagami distribution has been widely used to model echo amplitude distribution for tissue characterization. We explored the feasibility of using ultrasound Nakagami imaging as a model-based ASQ technique for assessing liver fibrosis. Standard ultrasound examinations were performed on 19 healthy volunteers and 91 patients with chronic hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 40 publications
2
25
1
Order By: Relevance
“…Picrosirius red-stained sections (100 × magnification) obtained from patients' livers with different stages of fibrosis from F0 to F4: (a) F0, (b) F1, (c) F2, (d) F3, and (e) F4. 3 Reproduced from Tsui et al 3 in accordance with the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/). Copyright © Tsui et al 3…”
Section: Cfarmentioning
confidence: 99%
See 3 more Smart Citations
“…Picrosirius red-stained sections (100 × magnification) obtained from patients' livers with different stages of fibrosis from F0 to F4: (a) F0, (b) F1, (c) F2, (d) F3, and (e) F4. 3 Reproduced from Tsui et al 3 in accordance with the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/). Copyright © Tsui et al 3…”
Section: Cfarmentioning
confidence: 99%
“…The above studies showed the feasibility of Nakagami imaging in assessing liver fibrosis, but the diagnostic performance (e.g., AUROC) was not investigated. In 2016, Tsui et al 3 reported that for 91 patients with chronic hepatitis B and C (biopsy: F0 = 4, F1 = 19, F2 = 23, F3 = 12, and F4 = 33), the AUROC for diagnosing fibrosis stages ≥F1, ≥F2, ≥F3, and ≥F4 with Nakagami imaging was 0.88, 0.84, 0.69, and 0.67 (p < 0.0001), respectively. Figures 10 and 11 show respectively B-mode ultrasound images and Nakagami images obtained from the healthy volunteers and patients with liver fibrosis (F0-F4).…”
Section: Nakagami Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the performance of Nakagami imaging for tissue characterization is less affected by different scanner settings. Nakagami imaging has demonstrated its capability for characterizing tissue properties and has shown promising results in many applications, such as cancer diagnosis, staging of liver fibrosis, and thermal ablation monitoring [20,21,22,23,24,25,26,27]. Although the Nakagami imaging has been used for many applications, it has not yet been applied to a tissue regeneration study.…”
Section: Introductionmentioning
confidence: 99%